Ukraine's Digital Economy Under Martial Law: Innovative Approaches and Legal Context - Pereguda, Yuliia; Stender, Svitlana; Rusnak, Alla; Khilukha, Oksana; Bielousov, Yaroslav (International Journal of Economics and Financial Issues, 2024)
This study investigates the sustainability of Ukraine's digital economy under martial law, focusing on the influence of cyber security innovations, fintech services, and legal regulations. Using a differential equation-based model, the research examines the dynamic relationships between technological innovation, regulatory measures, and cyber threats. The model demonstrates that sustainability increases exponentially with technological advancements, while regulatory measures and cyberattacks affect it linearly. Logistic regression analysis of survey data from 150 respondents, including policymakers, IT experts, and fintech professionals, reveals that legal regulations play the most significant role, increasing the likelihood of sustainability by 2.65 times. Cyber security innovations enhance sustainability by 1.90 times, and fintech services contribute by 1.52 times. The model’s accuracy was validated with a Receiver Operating Characteristic (ROC) curve, achieving an AUC score of 0.85, indicating strong predictive power. These findings provide essential insights for policymakers and business leaders, emphasising the need for adaptive regulations and continuous technological innovation to maintain digital infrastructure resilience in conflict settings. The results highlight the importance of fostering innovation ecosystems and enhancing legal frameworks to safeguard the digital economy during periods of instability, providing a roadmap for strengthening digital resilience.